A Comparison of the Stomatognathic and Neck Functions between Smokers and Non-smokers - Oğuzhan METE; Emine İPEK HALATCI; Serap ÇINAR; Sena ADANIR; Nezehat Özgül ÜNLÜER (Bezmiâlem Science, 2025)
Objective: This study aimed to compare smokers’ and non-smokers’ stomatognathic and neck functions. Methods: The study included 100 smokers and 96 non-smokers who did not have any chronic diseases. Temporomandibular and swallowing functions were evaluated as stomatognathic function components. Temporomandibular function with Fonseca Anamnestic Index (FAI) and swallowing function with Eating Assessment Tool (EAT-10) were assessed. The Neck Disability Index (NDI) was used to evaluate neck functions. Results: The FAI score of smokers was higher than non-smokers (p=0.005). According to FAI scores, 68 (68%) of smokers had the risk of temporomandibular disorder (TMD), whereas 48 (50%) of non-smokers had the risk of TMD. The risk of TMD was higher in smokers (p=0.013). The EAT-10 scores of smokers and non-smokers were similar (p=0.692). Four participants among smokers (4%) and 4 participants among non-smokers (4.1%) had a risk for the swallowing disorder. The risk for the swallowing disorder of smokers and non-smokers was similar (p>0.999). The NDI scores were similar between smokers and non-smokers (p=0.833). According to NDI, 38 (38%) and 38 (39.6%) participants in both smokers and non-smokers had no functional neck disability. The rate of functional neck disability of the groups was similar (p=0.304). Conclusion: It was found that the risk of temporomandibular dysfunction was higher in smokers than in non-smokers, but not for swallowing and neck function. Even in the absence of chronic disease, the risk of developing temporomandibular dysfunction in smokers should be kept in mind.